PENGARUH SENAM IRAMA TERHADAP PERKEMBANGAN MOTORIK KASAR ANAK - Hopipah, Neneng; Hidayat, Amat; Sina, Ibnu; Risna, Inten; Bayi Tabrani, Mohamad (LPPM Universitas Bina Bangsa, 2025)
Gross motor skills are an important aspect of children's physical development that needs to be developed from an early age. One activity considered effective in stimulating these skills is rhythmic gymnastics. This study aims to determine the effect of rhythmic gymnastics on the gross motor development of children aged 5–6 years enrolled at Masyarikul Anwar Pre-Primary Education in Serang Regency. This study used a quantitative approach with a quasi-experimental method with a pretest and posttest design. Fifteen children participated in the study. Data collection used an observation sheet covering indicators of balance, strength, and agility. The data were analyzed using a paired sample t-test using SPSS. Based on the analysis, a significant difference was found between the pretest and posttest scores, indicating an increase in gross motor skills after regular rhythmic gymnastics treatment. Therefore, rhythmic gymnastics can be used as a learning method to optimally support the physical development of early childhood.